Fatigue in patients with chronic inflammatory demyelinating polyneuropathy - R. A. Gapeshin; E. R. Barantsevich; D. I. Rudenko; T. R. Stuchevskaya; E. A. Gavrilova; M. S. Pushkaryov; A. A. Yakovlev; A. V. Gavrichenko; A. G. Smochilin (Неврология, нейропсихиатрия, психосоматика, 2021)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is a peripheral neuropathy, predominantly motor neuropathy, with a progressive or relapse-remitting course. Fatigue is a condition characterized by a physical or mental feeling of lack of energy or lack of motivation for action, which is often present in patients with CIDP.Objective: to assess the severity of asthenia in CIDP patients.Patients and methods. Examinations were made in 34 inpatients treated for documented CIDP that met the international European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) criteria. A study group included patients with CIDP, whereas a comparison group consisted of volunteers without psychiatric illness, who were compensated for somatic diseases.Results and discussion. In the patients with CIDP, the level of fatigue was found to be much higher than normal. Approximately half of the CIDP patients had obvious asthenia. However, the level of fatigue did not correlate with the severity of the course of CIDP.Conclusion. The findings suggest that fatigue is important in patients with CIDP that should be taken into account in the treatment of these patients.